Isavuconazole for treatment of invasive fungal diseases caused by more than one fungal species. Issue 7 (26th April 2018) - Marty, Francisco M.; Cornely, Oliver A.; Mullane, Kathleen M.; Ostrosky‐Zeichner, Luis; Maher, Rochelle M.; Croos‐Dabrera, Rodney; Lu, Qiaoyang; Lademacher, Christopher; Oren, Ilana; Schmitt‐Hoffmann, Anne‐Hortense; Giladi, Michael; Rahav, Galia; et al.
Summary: The optimal approach to treat invasive fungal disease (IFD) caused by more than one fungal species is unknown. We documented the efficacy and safety of isavuconazole for treatment of IFDs caused by more than one fungal species. VITAL was a single‐arm, international, open‐label study evaluating the efficacy and safety of isavuconazole (200 mg orally or intravenously every 8 hours for 48 hours, then once daily) for treatment of rare IFDs. The primary outcome was the overall response at Day 42; key secondary outcomes were overall responses at Day 84 and end of treatment (EOT), mortality at Days 42 and 84, and safety. This analysis includes patients with IFD caused by multiple fungal species. Fifteen patients were included in this analysis (including Aspergillus spp., n = 11; without Aspergillus spp., n = 4); median treatment duration was 97 days [range, 6‐544] days). Overall treatment success was observed in 2/15 patients (13.3%) at Days 42 and 84, and 2/14 (14.3%) at EOT. All‐cause mortality was 2/15 (13.3%) at Day 42 and 4/15 (26.7%) at Day 84. All patients had ≥1 treatment‐emergent adverse event (TEAE); 12 patients (80.0%) had serious TEAEs; TEAEs led to discontinuation of isavuconazole in two patients (13.3%). Isavuconazole may be useful to treat some IFDs caused by multiple fungal species.